PENDIDIKAN KESEHATAN MENGENAL DAN MENGATASI DISMENOREA DENGAN TERAPI JAHE MERAH - Monika Caterina (Nusantara Hasana Berdikari, 2021)
Menstruation is a natural process that occurs in women. Menstruation is regular bleeding from the uterus as a sign that the uterine organs have matured. Based on the incidence of menstrual pain in Indonesia, which is 54.89%, half of women in Indonesia experience menstrual pain/dysmenorrhea. Objective: To increase the knowledge of webinar participants regarding dysmenorrhea and its non-pharmacological therapy. Method: Health education is done using zoom meeting with 87 participant. Results: An increase in knowledge about dysmenorrhea and red ginger therapy can overcome dysmenorrhea after being given health education.